Azerbaijan : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
From the discussions, the paper reveals the vulnerability of the Azerbaijan banking system to conventional risk factors. Despite a stable macroeconomic environment and high margins of intermediation, the profitability of the banking system is on the decline. There has been an increase in the unemployment rate, maternal mortality rates, drop-out rates, and widespread use of unofficial user charges. The role of fiscal and monetary policies in response to an oil boom should be to facilitate a smooth transfer of resources from the non-oil traded sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet